Customer Reactions to Service Provider Overgenerosity - Hooman, Estelami (Institutional Knowledge at Singapore Management University, 2002)
Existing research in services marketing has mostly focused on service encounters in which the service provider fails to meet customer expectations. Service encounters in which customer expectations are exceeded have not been as thoroughly examined. This article focuses on service encounters characterized by service provider generosity: the act of giving customers value beyond their expectations. Utilizing an experimental research design, the authors demonstrate that consumer reactions to such behavior are moderated by the organizational level of the service provider as well as the existence of a past purchase history. Counter to conventional belief, under certain conditions, overgenerosity may hinder customer assessments of a service. The article concludes with a discussion of the implications for services marketing strategy and research.